Temporary Architecture for sharing - Salvator-John A. Liotta (Agathón)
The projects presented here outline an interdisciplinary research established between various international universities, public and private institutions – Politecnico di Milano, Università di Tokyo, Université Libre de Bruxelles, Triennale di Milano, Farm Cultural Park and Parco Archeologico di Agrigento – and conducted between 2011 and 2018. The paper outlines the premises, the theories, the methodologies, the constructive peculiarities and the results of these years of collaboration.